A Motor Task, Not Working Memory, Causes the Revelation Effect. - Hiroshi Miura; Yuji Itoh (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2024)
Performing a cognitive task prior to making a recognition judgment increases the probability of old responses, which is known as the revelation effect. The criterion shift account (Niewiadomski & Hockley, 2001) proposes that occupation of working memory causes the revelation effect. However, we proposed that working memory does not cause it. Two experiments were conducted to disconfirm the relationship between working memory and the revelation effect and to consider an alternative explanation that metacognition causes the effect. In Experiment 1, the revelation effect was caused by a finger movement task, which puts little or no load on working memory. In Experiment 2, a metacognitive instruction that a cognitive task would make subsequent recognition easier induced a conservative criterion shift. The finding that a simple motor task caused the revelation effect in Experiment 1 disconfirms the relationship between working memory and the revelation effect and extends the boundaries of the occurrence of the effect. The findings in Experiment 2 suggest that metacognition may be related to the occurrence of the revelation effect. This study implies a paradoxical aspect of human cognition in that metacognition, which usually makes cognition more effective and rational, may also cause an irrational phenomenon, the revelation effect.